THE IMPLEMENTATION OF METHODICS DEMONSTRATION WITH MEDIA REALIA TOWARD THE RESULT OF STUDENT LEARNING ON MICROSCOPES SUBJECT MATERIAL - Dian Eka Lestari; pramudiyanti pramudiyanti; rini rita marpaung (Universitas Lampung, 2013)
Base observation already being done at SMP Perintis 1 Bandar Lampung, method that utilized by teacher in learning still to methodic discourse. Predicted it that becomes its low causal factor the result of student biological learning on microscopes subject material. Preconceived method can increase the result of student learning is by applying combination demonstration method and media realia. Sample in observational is students at VII B as class of experiment and VII C as class of control. Sample establishment with cluster random's tech sampling. On experiment class by learning with combination methodics demonstration and media realia, and on class control to utilize discussion method. Observational Design is utilized pretest-posttest equivalen design. Data in observational is quantitative data and qualitative data. Acquired quantitative data of cognitive data student as mastery of concept that took by gives pretest and posttest. Qualitative data is gotten of psikomotor data student that taking to utilize performance test. Analysis data utilizes to t-test on trusty level 95% by use of program SPSS 17. The Result of observationaling showed that implement combination of methodics demonstration and media realia is significantly affect to the result of student learning on microscope subject material. Increasing happening on the result of student learning at experiment class with averagely N-gain 51,86. Averagely N-gain on experiment class higher than averagely N-gain on control class, so gets declared for that student concept mastery on microscopes subject material which utilize demonstration method with media realia highest than in comparison with discussion method. Known average percentage psikomotorik student on experiment class highest than at 61,59% compare to 36,14% in control class that utilize to methodic discussion. Key words: Demonstration method, media realia, microscope.